2022
DOI: 10.4102/hsag.v27i0.1751
|View full text |Cite
|
Sign up to set email alerts
|

Self-management experiences of youth following the unexpected loss of a family member to HIV

Abstract: Background: Death of a close family member is one of the most traumatic events in a person’s life. The way, in which this loss unfolds, varies from person to person and depends on how close you were with the deceased. It was unclear how youths experienced it to manage themselves during different stages of the bereavement process, after losing a near-family member to human immunodeficiency virus (HIV).Aim: The aim of this study was to understand the self-management of youth following the unexpected loss of a fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…25 26 Moreover, studies have confirmed the correlation between COVID-19 infection, death of family members and the decline in the quality of life of affected individuals. [27][28][29] Therefore, a portion of the decline in the quality of life of nurses observed in this study can be attributed to these factors. However, there are additional factors that contribute to this decline.…”
Section: Discussionmentioning
confidence: 74%
“…25 26 Moreover, studies have confirmed the correlation between COVID-19 infection, death of family members and the decline in the quality of life of affected individuals. [27][28][29] Therefore, a portion of the decline in the quality of life of nurses observed in this study can be attributed to these factors. However, there are additional factors that contribute to this decline.…”
Section: Discussionmentioning
confidence: 74%
“…Purposive sampling was based on the researcher’s judgement regarding participants who are typical of or especially knowledgeable about the study phenomenon. Participants were selected based on the features or characteristics which will help to explore the research questions (Brink et al, 2018 :159; Hlophe & Jooste 2022 :2). This research used semi-structured interviews with 11 young individuals who had lost a family member to HIV/AIDS.…”
Section: Methodsmentioning
confidence: 99%
“…The primary purpose was to request their assistance in determining the possible candidate for the study and refer them to the researcher. The possible participants had to be willing to participate in the study voluntarily (Hlophe & Jooste 2022 :3). Following consultations with patients, those who agree to see the researcher and where possible potential participants from the study were requested to go see the researcher in the private room for the interviews.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Youth going through the unexpected death of a family member, should be assisted with handling grief and setting up a positive intellect set around figuring it out their future. Youth are defined as persons between 18 and 25 years in the state or quality of being young, energetic, and immature [ 2 ].…”
Section: Introductionmentioning
confidence: 99%